2006
DOI: 10.1117/12.658057
|View full text |Cite
|
Sign up to set email alerts
|

Cycling conjugated polymers with different cations

Abstract: The ions present in the electrolyte in which a conjugated polymer actuator is cycled are known to affect performance. Understanding how force, response time, and strain are affected by ion size and other ion characteristics is critical to applications, but is not yet well understood. In this paper, we present the effect of alkali cation size on transport velocity and volume change in polypyrrole doped with dodecylbenzenesulfonate, PPy(DBS), which is a cation-transporting material. Volume change measured by mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The Cs + values, in contrast, drop rapidly towards zero, as if the Cs + ion moves much more slowly in the polymer, despite the smaller size of the non-hydrated ion. This apparent contradiction has also been observed in ion transport measurements in polypyrrole, where the largest, Li(H 2 O) x + ion, had the highest mobility [21]. We believe that the explanation for this apparent paradox is that the PPy film with inserted solvated water molecules (Li + and Na + ) is a quite different material than that with inserted non-solvated Cs + ions: the "naked" Cs + ion probably does not open the polymer up to the same degree as the solvated ions.…”
Section: Cation Effect On Strain As a Function Of Actuation Frequencymentioning
confidence: 79%
“…The Cs + values, in contrast, drop rapidly towards zero, as if the Cs + ion moves much more slowly in the polymer, despite the smaller size of the non-hydrated ion. This apparent contradiction has also been observed in ion transport measurements in polypyrrole, where the largest, Li(H 2 O) x + ion, had the highest mobility [21]. We believe that the explanation for this apparent paradox is that the PPy film with inserted solvated water molecules (Li + and Na + ) is a quite different material than that with inserted non-solvated Cs + ions: the "naked" Cs + ion probably does not open the polymer up to the same degree as the solvated ions.…”
Section: Cation Effect On Strain As a Function Of Actuation Frequencymentioning
confidence: 79%
“…The latter conclusion is based on the observation that actuation strain depends on the (solvated) ion size. 79…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on PPy(DBS) has shown that upon the first-ever reduction of the film, the out-of-plane volume increases approximately 60% as cations and water are pulled into polymer for the first time [28,31,51] (depending on the cation; these values are for Na + [52]). Upon re-oxidation, however, the film does not contract all the way back to its original thickness: there is a semi-permanent increase of ~25% due to ions and water that remain in the film.…”
Section: Discussionmentioning
confidence: 99%